Individual characteristics and their influence on employee retention in the Malaysian tourism industry - Ahmad, Nurul Aqilah (2016)
The purpose of this study is to examine the effects of individual characteristics; personal values, competencies and role perceptions as personal factors that influence organisational commitment and retention of employees in Malaysia’s tourism industry. This research intends to affirm the importance and effectiveness of individual characteristics in improving retention amongst employees in the tourism and hospitality industry of Malaysia. As organisational factors were mostly investigated by previous scholars, this is one of the few research to study individual factors in employees’ retention. This study extends the body of knowledge of personal values, competencies and role perception as individual factors of retention as there were limited researches being done in examining its antecedents. The Social Exchange Theory and the Job Characteristics Model were applied in supporting the proposed relationships and a total of eight hypotheses were proposed. The mixed method is used in analysing the effects of personal values, competencies, and role perception on organisational commitment and retention. The quantitative method is used in analyzing the data collected through questionnaire and the qualitative method is used in analyzing the data collected through two focus group discussions. The multistage sampling method was applied in the selection of respondents. For the qualitative data, there were two rounds of focus group discussion that were organized in June 2014 and February 2015. The first and second rounds of focus group discussion were participated by both management and operational level of employees. While for quantitative data, 474 employees from hotels, travel agencies and restaurants in the Klang Valley, Pahang, Johor and Penang participated in questionnaire survey. The data screening was carried out to eliminate missing values and outliers in the data collected. The reliability, multivariate assumption tests, and descriptive data analysis were conducted as well. A multiple regression analysis was employed to analyse the data and test the hypotheses in this study. The results of this study show that six out of eight hypotheses were supported. The findings show that personal values do not have significant relationships with retention and competencies do not have significant relationships with organisational commitment. However, personal values, competencies and role perception are found to be predictors of employees’ retention mediated by employees’ organisational commitment. The mediator effect of organisational commitment for the relationships between personal values, competencies and role perception; and retention were found to be statistically significant.